eHealth Solutions for Healthcare Disparities - Gibbons, Michael Christopher.; Gibbons, Michael Christopher. (Springer New York : Imprint: Springer, 2008)
Paralleling emerging trends in cyber-health technology, concerns are mounting about racial, ethnic, disparities in health care utilization and outcomes. eHealth Solutions for Health Care Disparities brings these currents together, challenging readers to use, promote, and develop new technology-based methods for closing these gaps. Edited by a leading urban health advocate and featuring 16 expert contributors, the book examines cyber-strategies with the greatest potential toward effective, equitable care, improved service delivery and better health outcomes for all. Chapters go well beyond the possibilities of the Electronic Medical Record to discuss emerging roles for information technology in promoting healthful behavior changes (e.g., nutrition, weight loss, smoking cessation), disease prevention (e.g., cancer, HIV), and healthcare utilization, patient education and medicine compliance). The rise of e-Patients and the transformation of the doctor-patient relationship are also discussed. Opportunities for Web based products and interventions are explored in terms of tracking disparities, improving healthcare utilization and health outcomes, reducing disparities and monitoring trends among patients, whether they have Internet capabilities or not. Among the book’s highlights: Why health care gaps still exist: individual, provider, and systemic factors. What information technology can bring to health care services. Current strategies in eHealth, public health informatics, and medical informatics. Technological disparities, and what can be done to reduce them. New paradigms in disparity research. The potential for eHealth in health care policy. For public health professionals, health care administrators and informaticians as well as graduate students in health behaviors, health promotion, and social epidemiology, eHealth Solutions for Health Care Disparities is a lucid map for an increasingly digital future.